Security and East-Med gas - Khadduri, W (Oxford Institute for Energy Studies, 2012)
The US Geological Survey (USGS) estimates that the entire Leviathan Basin holds a mean approximation of 1.7 bn barrels of recoverable crude oil and a mean of 122 trillion cubic feet (tcf) of recoverable gas reserves. The Levant Basin includes mostly offshore territories of Palestine, Israel, Lebanon and Syria, as well as territory off Cyprus. Reservoirs within the basin mainly contain Mesozoic and Paleogene sandstones, near shore marine and submarine sandstones and Jurassic and Cretaceous shelf-margin carbonates.